The attitudes of society towards disabled people with particular emphasis on people with Down syndrome - Nawalana, Anna; Majda, Anna (Nursing in the 21st Century, 2013)
THE ATTITUDES OF SOCIETY TOWARDS DISABLED PEOPLE WITH PARTICULAR EMPHASIS ON PEOPLE WITH DOWN SYNDROMEAim. Showing social attitudes towards disabled people with particular emphasis on people with Down syndrome.Materials and methods. Analysis of the available literature in accordance with the criteria of the research questions.Results. People with disabilities often evoke emotional reactions in society, such as anger, fear or pity. Lack of knowledge about disability poses a risk of perpetuation of existing stereotypes. People with Down syndrome are frequently characterized according to common patterns, like being infantile or asexual. Their appearance is often perceived as "a physical ugliness" and is a type of stigma. Disability  involves categorizing individuals into "better" and "worse", along with discriminatory practices.Conclusions. Over the centuries we can observe the evaluation of attitudes towards disabled people, including those with Down syndrome. Extremely negative attitudes, such as, elimination or isolation are being gradually replaced by more favorable attitudes. Unfortunately, in the social environment, including the medical one, there are still some harmful stereotypes about disabled people, which together with prejudice and stigmatization process make them second-class individuals.